Plant Diversity In Ancol Coastal Area, Semidang Alas Maras District, Seluma Regency As A Teaching Material To Improve Learning Outcomes On The Classification Of Living Things For Grade IX Students At SMPN 14 Seluma - Susanti, Yesi; B, Basinun; Topano, Andrian (Journal of Innovation in Research, Education and Culture (JIREC), 2024)
The aim of this research is to determine 1) the diversity of plants in the Ancol beach area as teaching material to improve learning outcomes in the material on the classification of living creatures for class IX students at SMP Negeri 14 Seluma, 2) the influence of the results of identifying plant diversity in the Ancol beach area, Kec. Semidang Alas Maras District. Seluma as teaching material to improve learning outcomes in the material on the classification of living things for class IX students at SMP Negeri 14 Seluma. This type of research is quantitative correlational research with a quantitative descriptive approach. The research sample of class IX students at SMP Negeri 14 Seluma was 30 people using a total sampling technique. Data collection techniques are observation, tests and documentation. Data analysis used quantitative with the t test. The results of the research showed that the plants on the coast of Ancol, Semidang Alas Maras District, Seluma Regency consisted of 15 types of plants, namely Rhizopora apiculata (fire mangrove), Rhizopora mucronata (ringworm mangrove), Peking grass (Zoysia matrella (L.)Merr), cypress (Casuarina equisetifolia L), horsetail (Ipomea pes caprae), Terminalia catappa L (sea hyacinth), wedelia blifora (Sea chrysanthemum), sea fern (Acrostichum aureum), Cyperus Esculentus (yellow sesame grass ), ketapang (Terminalia catappa L), bitter jukut (Axonopus compressus Swartz), davallia solida (rabbit's foot fern), needle grass (Andropogon aciculatus), coconut (Cocos nucifera), sea pandan (Poaceae and Arecaceae). There is an influence on the results of identifying plant diversity in the coastal area of Ancol District. Semidang Alas Maras District. Seluma as teaching material for improving learning outcomes in the material on the classification of living things for class IX students at SMP Negeri 14 Seluma tcount > ttable 2.03011 and p value 0.000 < 0.05. . Keywords: Diversity, Plants, Teaching Materials, Learning Outcomes